Dinamika Ekonomi Politik Industri Penerbitan Pers Lokal: Praktek Komodifikasi Dan Spasialisasi Di Kota Kupang - Yoseph Andreas Gual (Jurnal Komunikasi, 2014)
AbstractThis article moves from the reality of the life of a newspaper in the city of East Nusa Tenggara (NTT), which is in line with the changing social and political movements in Indonesia, especially from the New Orde to the Reformation. From only one newspaper then a dozen newspapers, back leaving five newspapers at last. This phenomenon leaves the question, the dynamics of what is going on there? In a communication perspective, this phenomenon can be explained by the political economy approach. Then the above phenomenon as a case of political economy approach is approached by the media, especially the commodification and spatialization by Vincent Mosco. From the search results discovered that the commodification and spatialization carried by newspapers in the city. But the practice is different from one media to another media, especially among the local newspaper that affiliated with the national media. Many local newspaper owned and managed by local communities.AbstrakArtikel ini bergerak dari realitas kehidupan surat kabar di Kota Kupang Nusa Tenggara Timur (NTT) yang mengalami perubahan sejalan dengan gerakan sosial politik di Indonesia terutama pada masa Orde Baru ke masa Reformasi. Dari hanya satu koran lalu menjadi belasan koran lalu kembali menyisakan lima koran. Fenomena ini menyisakan pertanyaan, dinamika apa yang sedang terjadi di sana? Dalam perspektif komunikasi, fenomena ini dapat dijelaskan dengan pendekatan ekonomi politik. Maka fenomena di atas sebagai sebuah kasus didekati dengan pendekatan ekonomi politik media terutama komodifikasi dan spasialisasi menurut Vincent Mosco. Dari hasil penelusuran ditemukan bahwa komodifikasi dan spasialisasi dilakukan oleh koran-koran di Kota Kupang. Namun prakteknya berbeda antara satu media dengan media lain terutama antara koran lokal yang berafiliasi dengan media nasional dengan koran yang murni dimiliki dan dikelola oleh masyarakat lokal.